Biomodifying the 'natural': from Adaptive Regulation to Adaptive Societal Governance. Issue 1 (30th June 2022) - Mourby, Miranda; Bell, Jessica; Morrison, Michael; Faulkner, Alex; Li, Phoebe; Bicudo, Edison; Webster, Andrew; Kaye, Jane
Abstract: Biomodifying technologies—such as gene editing, induced pluripotent stem cells, and bioprinting—are being developed for a wide range of applications, from pest control to lab-grown meat. In medicine, regulators have responded to the challenge of evaluating modified 'natural' material as a therapeutic 'product' by introducing more flexible assessment schemes. Attempts have also been made to engage stakeholders across the globe on the acceptable parameters for these technologies, particularly in the case of gene editing. Regulatory flexibility and stakeholder engagement are important, but a broader perspective is also needed to respond to the potential disruption of biomodification. Our case-study technologies problematize basic ideas—such as 'nature', 'product', and 'donation'—that underpin the legal categories used to regulate biotechnology. Where such foundational concepts are rendered uncertain, a socially responsive and sustainable solution would involve exploring evolutions in these concepts across different societies. We suggest that the global observatory model is a good starting point for this 'Adaptive Societal Governance' approach, in which a self-organizing network of scholars and interested parties could carry out the multi-modal (meta)analyses needed to understand societal constructions of ideas inherent to our understanding of 'life'.